Physicochemical Properties, Mineral Content, Antioxidant Activities, and Microbiological Quality of Bupleurum spinosum Gouan Honey from the Middle Atlas in Morocco - Hassan Laaroussi; Toufik Bouddine; Meryem Bakour; Driss Ousaaid; Badiaa Lyoussi (Journal of Food Quality)
Monofloral honeys (Bupleurum Spinosum) collected from different geographical locations of Moroccan Middle Atlas were evaluated for various potential attributes. For physicochemical parameters, the results showed the following values: pH (4.02–4.81); free acidity (12.16–31.85 mEq/kg); lactonic acidity (4.98–14.14 mEq/kg); total acidity (18.37–45.53 mEq/kg); moisture (15.81–19.20%); ash (0.21–0.55); electrical conductivity (427.38–682.16 mS/cm); diastasic activity (10.76–26.01); TSS (80.40–84.20%); melanoidins (0.21–1.15), and Pfund scale (30.47–175.53 mm). Potassium was the most important mineral among the tent evaluated elements, followed by sodium and calcium. All tested samples have high antioxidant activities and correlate with phenols, flavonoids, and ascorbic acid content. In regards to safety (sulfite-reducing clostridia and Salmonella spp.) and sanitary quality (faecal coliforms), all honey samples were negative. In addition, low counts of yeast and molds were detected, and the values of total aerobic mesophilic bacteria and Bacillus Sp. confirm the good quality of honey. The outcome of this study showed that all samples have good physicochemical properties, high antioxidant activities, and acceptable microbiological state, respecting the quality control criteria set by the international norms.